Sediment response to stream restoration in an agricultural watershed - John W. Clune; Gregory B. Noe; Matthew Cashman; Jessica D. DeWitt; Joseph M. Bell; Mitchell R. Weaver; James E. Colgin; Thomas R. Doody; Eliza L. Gross; Victor S. Cortes (Ecological Engineering, 2026)

Machine learning-assisted gait analysis for lameness detection in heterogeneous dog populations - Lyndie Mitchell; Matthew Scott; Kirsten Häusler; Chiara Adami; Michael Sutcliffe; Matthew Allen (The Veterinary Journal, 2026)

Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

Semi‐Natural Habitats Buffer the Effects of Crop Diversification on Arthropod Pest Control Services in Agricultural Landscapes - Thomas Perrot; Léa Beaumelle; Eva Thomine; Yann Tricault; Nicolas Desneux; Matthias Albrecht; Péter Batáry; Felix Bianchi; Klaus Birkhofer; Aliette Bosem Baillod; Rebecca Chaplin‐Kramer; Anne‐Marie Cortesero; et al. (Ecology Letters, 2026)
Crop diversification is a promising strategy to strengthen pest control services in agricultural landscapes. Diversifying crops may limit pests through host crop dilution or by enhancing top‐down control by their enemies. However, crop diversification may also benefit generalist pests through higher resource continuity. Using a large‐scale dataset encompassing 742 landscapes across 13 countries, we assessed the impact of landscape‐scale crop diversity on the abundance of natural enemies, the potential for biological control, and insect pest abundance. Crop diversification did not increase the overall abundance of natural enemies or the potential for biological pest control. Instead, crop diversity primarily favoured the abundance of specialist natural enemies and pests in highly simplified landscapes, an effect that was reduced in landscapes with high proportions of semi‐natural habitats. Lastly, low proportions of host crops in the landscape were associated with higher abundances of natural enemies. Taken together, our results indicate that crop diversification is not a ‘one size fits all’ strategy to control agricultural pests, and that other landscape characteristics, such as high amounts of semi‐natural habitats, must be considered to enhance biological pest control services.

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

Drivers of fine-scale space use and grazing patterns of juvenile parrotfish on western Atlantic reefs - David P. Kochan; Melanie M. Esch; Robert Y. Fidler; Matthew D. Mitchell; Manuel González-Rivero; Alastair R. Harborne (Coral Reefs, 2026)

Non-Candida fungal cholecystitis - an uncommon occurrence even in the right host - Mitchell G. Dumais; Mary M. Czech; Mustafa A. Hyder; Rachel R. Lee; Juan C. Gea-Banacloche; Christopher G. Kanakry; Sun A. Kim; Bindu Adhikari; Matthew D. Surette; Adrian M. Zelazny; Amir Seyedmousavi; Jennifer M. Cuellar-Rodriguez (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Invasive fungal infections (IFI) are a significant cause of morbidity and mortality in hematologic malignancy patients and hematopoietic cell transplant (HCT) recipients. Mold cholecystitis has rarely been described. We present a case of disseminated Lomentospora prolificans , that had recrudescence of symptoms with acute cholecystitis. Treatment included a temporary cholecystostomy and administration of the novel antifungal fosmanogepix. At 6 weeks post-HCT, the patient underwent cholecystectomy and completed a course of fosmanogepix, leading to resolution of her infection. Here we review the published literature on non- Candida fungal cholecystitis, underlying risk factors and treatment.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Establishing baseline control water values for differential scanning calorimetry (DSC) in cryoprotectant exploration - P.U. Ashvin Iresh Fernando; Nick Mitchell; Olivier Montmayeur; Brianna M. Fernando; Matthew A. Fort; John G. Tsavalas; Emily Asenath-Smith (Cryobiology, 2025)

A defense of the circular economy - Julian Kirchherr; Mitchell P. Jones; Martin Geissdoerfer; Matthew Coffay (Journal of Industrial Ecology, 2025)
The notion of circular economy (CE) has been trending among policymakers, businesses, and academia for over a decade. Sometimes poorly understood and often misrepresented as a one‐size‐fits‐all solution to environmental problems without economic trade‐offs, the concept has recently drawn considerable criticism. According to its critics, the CE (1) rebrands existing concepts without clarity, (2) makes unrealistic environmental promises, (3) oversimplifies and overlooks critical factors, (4) clashes with societal values and norms, (5) fails in practical business applications, and (6) serves as a capitalist tool for Western interests. In this paper, we critically review these criticisms of the CE, many of which are not based on empirical realities, are obsolete, or originate in oversimplified interpretations of the circle metaphor. We argue that CE is an “umbrella” framing for existing concepts with a relatively concrete definition. Formerly corporate led, CE has matured into an academically dominated field, backed by substantial technical literature, new sub‐fields led by social scientists, and an increasingly advanced and detailed understanding of previous simplifications. Empirical evidence is emerging that CE can be operationalized and scaled, provide considerable environmental benefits, and can align with societal values and priorities. While easy to criticize, the hope and momentum that the CE has sparked is creating tangible benefits over other sustainability‐oriented concepts. Further research is required to establish its long‐term advantages, drawbacks, and complementarities with alternative approaches.

Publisher Correction to: Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)

Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)
Urban populations face increasing vulnerability to extreme heat events, particularly in rapidly urbanising Global South cities where environmental exposure intersects with socioeconomic inequality and limited healthcare access. This study quantifies heat vulnerability across Johannesburg, South Africa, by integrating high-resolution environmental data with socio-economic and health metrics across 135 urban wards. We examine how historical urban development patterns influence contemporary vulnerability distributions using principal component analysis and spatial statistics. Environmental indicators (Land Surface Temperature (LST), vegetation indices, and thermal field variance) were combined with socioeconomic and health variables (including indicators on crowded dwellings and healthcare access, self-reporting of chronic diseases) in a comprehensive vulnerability assessment. Principal Component Analysis revealed three primary dimensions explaining 56.6% (95% CI: 52.4–60.8%) of the total variance: urban heat exposure (31.5%), health status (12.8%), and socio-economic conditions (12.3%). Built-up areas showed weak but significant correlations with heat indices (ρ = 0.28, p < 0.01), while higher poverty levels demonstrated moderate positive correlations with LST (ρ = 0.41, p < 0.001). The spatial analysis identified significant clustering of vulnerability (Global Moran's I = 0.42, p < 0.001), with distinct high-vulnerability clusters in historically disadvantaged areas. Alexandra Township showed the highest vulnerability(HVI score: 0.87, LST: 29.8 °C ± 0.4 °C, NDVI: 0.08 ± 0.02), with factors characterising the high vulnerability in that area including limited healthcare access and extreme heat exposure. Northern suburbs formed a significant low-vulnerability cluster (Mean HVI = 0.23 ± 0.07, p < 0.001), benefiting from greater vegetation coverage and better healthcare access. These findings demonstrate how historical planning decisions continue to shape contemporary environmental health risks, with vulnerability concentrated in areas of limited healthcare access and high extreme heat exposure. Results suggest the need for targeted interventions that address both environmental and social dimensions of heat vulnerability, particularly focusing on expanding healthcare access in identified hotspots and implementing community-scale green infrastructure in high-risk areas. This study provides an evidence-based framework for prioritising heat-resilience initiatives in rapidly urbanising Global South cities while highlighting the importance of addressing historical inequities in urban adaptation planning.

GMFOLD: Subgraph matching for high-throughput DNA-aptamer secondary structure classification and machine learning interpretability - Paolo Climaco; Noelle M. Mitchell; Matthew J. Tyler; Kyungae Yang; Anne M. Andrews; Andrea L. Bertozzi (Mathematical Biosciences, 2025)

Victor diamonds – replacement of carbon and nitrogen in the central Superior Craton mantle root associated with the Midcontinent Rift event - Luisa D. V. Carvalho; Anetta Banas; Pamela Wescott; Mitchell Galarneau; Kelsey Graversen; Richard Stern; Ingrid Chinn; Heidi E. Höfer; Karlis Muehlenbachs; Matthew Steele-MacInnis; David Fisher; Julie Kong; et al. (Mineralogy and Petrology, 2025)

Modeling Wetland Resources for Spring Migratory Waterbirds Under Different Agricultural Management Scenarios in the Iowa Portion of the Prairie Pothole Region, USA - Mark E. Mitchell; Michael J. Anteau; Aaron T. Pearse; Tammy Newcomer-Johnson; Jay Christensen; William Crumpton; Brian Dyson; Timothy J. Canfield; Matthew Helmers; David Green; Kenneth J. Forshay (Wetlands, 2025)
Constructed water quality wetlands, designed to accept tile drainage and surface runoff, are a promising solution for reducing surface water nutrient loading from agricultural systems. In addition to their water quality benefits, these systems may also offset losses of migratory waterbird stopover sites resulting from historical and future agricultural drainage modernization. To assess this possibility, we developed spatially explicit habitat models informed with expert opinion to explore the: 1) potential of water quality wetlands to provide suitable stopover resources for waterbirds during spring migration; and 2) the extent these wetlands can offset likely losses of stopover resources due to drainage modernization. We focused our modeling on the Iowa portion of the Prairie Pothole Region of North America as it was a historically important area within this vital region for waterbirds, but it has experienced widespread subsurface drainage. Model results indicate that unmitigated drainage modernization is likely to have a large negative effect on spring migratory resources for dabbling ducks and shorebirds and minimal effect on diving ducks. Water quality wetland installations are likely to provide habitat for dabbling and diving ducks, but wetland installation is unlikely to completely offset habitat losses for dabbling ducks and shorebirds. Drainage modernization aside, our results indicate that water quality wetlands can address several environmental issues associated with agricultural expansion and intensification by improving water quality and providing wetland resources for waterbirds and other organisms. Field-scale research is needed to validate these results.

Mapping illegal trade routes of live cheetahs from the Horn of Africa to the Arabian Peninsula - Paul H. Evangelista; Nicholas E. Young; Darin K. Schulte; Patricia D. Tricorache; Matthew W. Luizza; Sarah M. Durant; Kelly W. Jones; Nicholas Mitchell; Tomas Maule; Abdullahi H. Ali; Redae T. Tesfai; Peder S. Engelstad (Conservation Biology, 2025)
Less than 7000 cheetahs ( Acinonyx jubatus ) persist in Africa. Although human–wildlife conflict, habitat degradation, and loss of prey are major threats to cheetah populations, illegal trade in live cubs for pets may have the most significant impact on populations in the Horn of Africa. We developed a novel, stepwise decision support tool to predict probable trafficking routes by leveraging the power of distinct modeling approaches. First, we created a cheetah habitat suitability index (HSI) to determine where source cheetah populations may occur. We then created a trafficking network model linking known and predicted cheetah populations with documented destinations in the Arabian Peninsula. A significant area in Eastern Ethiopia and Northern Somalia was estimated to harbor undocumented cheetahs. When these predicted populations were used as a supply source, the trafficking network model showed multiple routes passing through Somaliland and across the Gulf of Aden to Yemen, supporting the notion that undocumented cheetahs may be supplying pet market demands. Though we demonstrate how our decision support tool can inform law enforcement, conservation strategies, and community engagement, we caution that our results are not fully validated due to limited accessibility, alternative trafficking routes, and the cryptic nature of illegal wildlife trade.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Narrow Margins: Aerobic Performance and Temperature Tolerance of Coral Reef Fishes Facing Extreme Thermal Variability - Grace O. Vaughan; Daniel M. Ripley; Matthew D. Mitchell; Dain McParland; Jacob L. Johansen; Holly A. Shiels; John A. Burt (Global Change Biology, 2025)
Climate change is driving rising average sea temperatures and the intensification of thermal variability. Tropical coral reef fishes have evolved under thermally stable conditions to function optimally within a narrow temperature range, with many currently living close to their upper thermal limits. However, recent work has demonstrated that some species possess additional capacity, such as reductions in basal metabolic rates (i.e., ‘plastic floors’), to compensate for the acute effects of thermal challenges when assessed over multigenerational timeframes. In this study, we use the ‘plastic floors and concrete ceilings’ hypothesis to generate and then test predictions regarding the thermal physiology of reef fishes in the world's hottest and most thermally variable coral reef ecosystem (southern Arabian/Persian Gulf). By comparing three species of reef fishes ( Scolopsis ghanam , Ecsenius pulcher and Cheilodipterus novemstriatus ) from the southern Arabian/Persian Gulf, with an annual temperature range of 18.0°C–36.5°C, to conspecifics from nearby but more thermally benign (~21.0°C–32.0°C) reefs in the Gulf of Oman, we find enhanced upper thermal limits and a broadening of the temperature performance curves for aerobic scope in the Arabian/Persian Gulf, but no evidence for changes in basal metabolic rates (‘plastic floors’). Despite these conserved increases in temperature tolerance, the summer thermal safety margins of Arabian/Persian Gulf fishes were 1.47°C lower than those of conspecifics from the Gulf of Oman, demonstrating that while the temperature tolerance of tropical coral reef fishes is somewhat plastic over multigenerational timeframes, its rate of change is likely insufficient to keep pace with the rising average temperatures and growing thermal variability expected under climate change.

Contrasting population declines and drivers of ecological refuge for two range-restricted amphibians - Emily P. Hoffmann; Kim Williams; Christine Taylor; Grzegorz Skrzypek; Matthew R. Hipsey; Nicola J. Mitchell (Biodiversity and Conservation, 2025)

Distinct Longitudinal Changes in EEG Measures Reflecting Functional Network Disruption in ALS Cognitive Phenotypes - Marjorie Metzger; Stefan Dukic; Roisin McMackin; Eileen Giglia; Matthew Mitchell; Saroj Bista; Emmet Costello; Colm Peelo; Yasmine Tadjine; Vladyslav Sirenko; Lara McManus; Teresa Buxo; et al. (Brain Topography, 2025)
Amyotrophic lateral sclerosis (ALS) is characterised primarily by motor system degeneration, with clinical evidence of cognitive and behavioural change in up to 50% of cases. We have shown previously that resting-state EEG captures dysfunction in motor and cognitive networks in ALS. However, the longitudinal development of these dysfunctional patterns, especially in networks linked with cognitive-behavioural functions, remains unclear. Longitudinal studies on non-motor changes in ALS are essential to further develop our understanding of disease progression, improve care and enhance the evaluation of new treatments. To address this gap, we examined 124 ALS individuals with 128-channel resting-state EEG recordings, categorised by cognitive impairment (ALSci, n = 25), behavioural impairment (ALSbi, n = 58), or non-impaired (ALSncbi, n = 53), with 12 participants meeting the criteria for both ALSci and ALSbi. Using linear mixed-effects models, we characterised the general and phenotype-specific longitudinal changes in brain network, and their association with cognitive performance, behaviour changes, fine motor symptoms, and survival. Our findings revealed a significant decline in $$\:θ\:$$ -band spectral power over time in the temporal region along with increased $$\:{γ\:}_{l}$$ -band power in the fronto-temporal region in the ALS group. ALSncbi participants showed widespread β-band synchrony decrease, while ALSci participants exhibited increased co-modulation correlated with verbal fluency decline. Longitudinal network-level changes were specific of ALS subgroups and correlated with motor, cognitive, and behavioural decline, as well as with survival. Spectral EEG measures can longitudinally track abnormal network patterns, serving as a candidate stratification tool for clinical trials and personalised treatments in ALS.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Assessing the effect of multispecies interactions on precautionary reference points using an ensemble modelling approach: A North Sea case study - Michael A. Spence; James A. Martindale; Khatija Alliji; Hayley J. Bannister; Robert B. Thorpe; Nicola D. Walker; Peter J. Mitchell; Matthew R. Kerr; Paul J. Dolder (Fisheries Research, 2024)

Flood prevention benefits provided by Canadian natural ecosystems - Gabriela T. Duarte; Richard Schuster; Marc Edwards; Camille O. Dallaire; Ágnes Vári; Matthew G.E. Mitchell (Ecosystem Services, 2024)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

The 2019 pumice raft forming eruption of Volcano-F (Volcano 0403–091) and implications for hazards posed by submerged calderas - Isobel A. Yeo; Iona M. McIntosh; Scott E. Bryan; Kenichiro Tani; Matthew Dunbabin; Katherine J. Dobson; Samuel J. Mitchell; Patrick C. Collins; Michael A. Clare; Henrietta Cathey; Isikeli Duwai; Philipp A. Brandl; et al. (Journal of Volcanology and Geothermal Research, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Ecosourcing for resilience in a changing environment - Peter B. Heenan; William G. Lee; Matt S. McGlone; James K. McCarthy; Caroline M. Mitchell; Matthew J. Larcombe; Gary J. Houliston (New Zealand Journal of Botany, 2024)

The importance of crowdsourced observations for urban climate services - Timothy D. Mitchell; Matthew J. Fry (International Journal of Climatology, 2024)
Crowdsourced observation networks are typically much more dense than those maintained by National Meteorological Services, and sample a much wider range of local climates. This offers an opportunity to build observed climatologies that are more representative of lived experience, particularly in cities. This study provides a worked example to show their potential for improving operational climate services, and to identify the challenges to realizing that potential. To demonstrate the concept, data from personal weather stations, obtained through citizen science, are used to build an observed record of daily maximum temperatures in 2020 in Manchester (UK). This record is compared to the standard baseline used in a current climate service, showing a substantial increase in the estimated heat hazard. If such potential benefits are to be realized in a climate service, it will be necessary to first build an alternative observed baseline of decadal length and at national or international scale. This requires further work to acquire, quality‐control, exposure‐control and map the crowdsourced observations.

Drought impact on peri-urban farmers’ mental health in semi-arid Ghana: The moderating role of personal social capital - Matthew Abunyewah; Seth Asare Okyere; Seth Opoku Mensah; Michael Erdiaw-Kwasie; Thayaparan Gajendran; Mitchell K. Byrne (Environmental Development, 2024)

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

A review of ecosystem services from edge-of-field practices in tile-drained agricultural systems in the United States Corn Belt Region - Mark E. Mitchell; Tammy Newcomer-Johnson; Jay Christensen; William Crumpton; Brian Dyson; Timothy J. Canfield; Matthew Helmers; Kenneth J. Forshay (Journal of Environmental Management, 2023)

Understanding climate change adaptation in Ghana: The role of climate change anxiety, experience, and knowledge - Matthew Abunyewah; Michael Odei Erdiaw-Kwasie; Alex O. Acheampong; Patrick Arhin; Seth Asare Okyere; Kerstin Zanders; Louis Kusi Frimpong; Mitchell K. Byrne; Jonatan Lassa (Environmental Science & Policy, 2023)

More than greening: Using a novel index to assess restorative nature and vulnerability relationships - Tahia Devisscher; Taelynn Lam; Joanne Fitzgibbons; Ingrid Jarvis; Derek Li; Matthew G. E. Mitchell (Ambio, 2023)

Juvenile waiting stage crown‐of‐thorns sea stars are resilient in heatwave conditions that bleach and kill corals - Maria Byrne; Dione J. Deaker; Mitchell Gibbs; Paulina Selvakumaraswamy; Matthew Clements (Global Change Biology, 2023)
The juveniles of predatory sea stars can remain in their recruitment–nursery habitat for some time before their ontogenetic shift to the adult habitat and diet. These small juveniles are vulnerable to a range of factors with their sensitivity amplified by climate change‐driven ocean warming. We investigate the thermal tolerance of the waiting stage herbivorous juveniles of the keystone coral predator, the crown‐of‐thorns sea star (COTS, Acanthaster sp.), in context with the degree heating weeks (DHW) model that predicts coral bleaching and mass mortality. In temperature treatments ranging from +1 to 3°C in prolonged heatwave acclimation conditions, the juveniles exhibited ~100% survival in DHW scenarios that trigger coral bleaching (4 DHW), resulting in mass mortality of corals (8 DHW) and extreme conditions well beyond those that kill corals (12 DHW). This indicates that herbivorous juvenile COTS are far more resistant to heatwave conditions than the coral prey of the adults. The juveniles exhibited higher activity (righting) and metabolic rate after weeks in increased temperature. In separate acute temperature experiments, the upper thermal limit of the juveniles was 34–36°C. In a warming world, juvenile COTS residing in their coral rubble nursery habitat will benefit from an increase in the extent of this habitat due to coral mortality. The juveniles have potential for long‐term persistence as herbivores as they wait for live coral to recover before becoming coral predators, thereby serving as a proximate source of COTS outbreaks on reefs already in a tenuous state due to climate change.

Life cycle cost, energy, and carbon emissions of molds for precast concrete: Exploring the impacts of material choices and additive manufacturing - Kristina O. Armstrong; Dipti Kamath; Xianhui Zhao; Mitchell L. Rencheck; Halil Tekinalp; Matthew Korey; Diana Hun; Soydan Ozcan (Resources, Conservation and Recycling, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Food tree selection by an arboreal marsupial: Implications for timber harvest - Matthew K. Mitchell; Anthony R. Rendall; Matthew J. Lefoe; Desley A. Whisson (Forest Ecology and Management, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

A redesign of the toothpaste tube using green QFD II for improved usability and sustainability - Danielle S. Angtuaco; Nathan Mitchell A. Barria; Joshua Matthew C. Lee; Jazmin C. Tangsoc; Anthony Shun Fung Chiu; Jose Edgar Mutuc (Journal of Cleaner Production, 2023)

Monitoring threatened species with environmental DNA and open ecological data: Local distribution and habitat preferences of scalloped hammerhead sharks (Sphyrna lewini) - Alyssa M. Budd; Tom Schils; Madalyn K. Cooper; Mitchell B. Lyons; Matthew S. Mills; Mari E. Deinhart; Agnès Le Port; Roger Huerlimann; Jan M. Strugnell (Biological Conservation, 2023)

Neither myonuclear accretion nor a myonuclear domain size ceiling is a feature of the attenuated hypertrophic potential of aged human skeletal muscle - Matthew S. Brook; Daniel J. Wilkinson; Janelle Tarum; Kyle W. Mitchell; Jonathan L. Lund; Bethan E. Phillips; Nathaniel J. Szewczyk; Fawzi Kadi; Paul L. Greenhaff; Ken Smith; Philip J. Atherton (GeroScience, 2023)
Ageing limits growth capacity of skeletal muscle (e.g. in response to resistance exercise), but the role of satellite cell (SC) function in driving this phenomenon is poorly defined. Younger (Y) (~ 23 years) and older (O) men (~ 69 years) (normal-weight BMI) underwent 6 weeks of unilateral resistance exercise training (RET). Muscle biopsies were taken at baseline and after 3-/6-week training. We determined muscle size by fibre CSA (and type), SC number, myonuclei counts and DNA synthesis (via D 2 O ingestion). At baseline, there were no significant differences in fibre areas between Y and O. RET increased type I fibre area in Y from baseline at both 3 weeks and 6 weeks (baseline: 4509 ± 534 µm 2 , 3 weeks; 5497 ± 510 µm 2 P < 0.05, 6 weeks; 5402 ± 352 µm 2 P < 0.05), whilst O increased from baseline at 6 weeks only (baseline 5120 ± 403 µm 2 , 3 weeks; 5606 ± 620 µm 2 , 6 weeks; 6017 ± 482 µm 2 P < 0.05). However, type II fibre area increased from baseline in Y at both 3 weeks and 6 weeks (baseline: 4949 ± 459 µm 2 , 3 weeks; 6145 ± 484 µm 2 ( P < 0.01), 6 weeks; 5992 ± 491 µm 2 ( P < 0.01), whilst O showed no change (baseline 5210 ± 410 µm 2 , 3 weeks; 5356 ± 535 µm 2 ( P = 0.9), 6 weeks; 5857 ± 478 µm 2 ( P = 0.1). At baseline, there were no differences in fibre myonuclei number between Y and O. RET increased type I fibre myonuclei number from baseline in both Y and O at 3 weeks and 6 weeks with RET (younger: baseline 2.47 ± 0.16, 3 weeks; 3.19 ± 0.16 ( P < 0.001), 6 weeks; 3.70 ± 0.29 ( P < 0.0001); older: baseline 2.29 ± 0.09, 3 weeks; 3.01 ± 0.09 ( P < 0.001), 6 weeks; 3.65 ± 0.18 ( P < 0.0001)). Similarly, type II fibre myonuclei number increased from baseline in both Y and O at 3 weeks and 6 weeks (younger: baseline 2.49 ± 0.14, 3 weeks; 3.31 ± 0.21 ( P < 0.001), 6 weeks; 3.86 ± 0.29 ( P < 0.0001); older: baseline 2.43 ± 0.12, 3 weeks; 3.37 ± 0.12 ( P < 0.001), 6 weeks; 3.81 ± 0.15 ( P < 0.0001)). DNA synthesis rates %.d −1 exhibited a main effect of training but no age discrimination. Declines in myonuclei addition do not underlie impaired muscle growth capacity in older humans, supporting ribosomal and proteostasis impairments as we have previously reported.

South American morels in the Elata group: mitosporic states, distributions, and commentary - Donald H. Pfister; Rosanne Healy; Katherine F. LoBuglio; Giuliana Furci; James Mitchell; Matthew E. Smith (Mycological Progress, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Fitness effects of somatic mutations accumulating during vegetative growth - Mitchell B. Cruzan; Matthew A. Streisfeld; Jaime A. Schwoch (Evolutionary Ecology, 2022)
The unique life form of plants promotes the accumulation of somatic mutations that can be passed to offspring in the next generation, because the same meristem cells responsible for vegetative growth also generate gametes for sexual reproduction. However, little is known about the consequences of somatic mutation accumulation for offspring fitness. We evaluate the fitness effects of somatic mutations in Mimulus guttatus by comparing progeny from self-pollinations made within the same flower (autogamy) to progeny from self-pollinations made between stems on the same plant (geitonogamy). The effects of somatic mutations are evident from this comparison, as autogamy leads to homozygosity of a proportion of somatic mutations, but progeny from geitonogamy remain heterozygous for mutations unique to each stem. In two different experiments, we find consistent fitness effects of somatic mutations from individual stems. Surprisingly, several progeny groups from autogamous crosses displayed increases in fitness compared to progeny from geitonogamy crosses, likely indicating that beneficial somatic mutations occurred in some stems. These results support the hypothesis that somatic mutations accumulate during vegetative growth, but they are filtered by different forms of selection that occur throughout development, resulting in the culling of expressed deleterious mutations and the retention of beneficial mutations.

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

From quartz curvature to late Holocene mobility at Spring Cave, Western Cape, South Africa - Benjamin Davies; Matthew J. Douglass; David R. Braun; John Parkington; Mitchell J. Power; J. Tyler Faith (Archaeological and Anthropological Sciences, 2022)

Drivers of fine‐scale diurnal space use by a coral‐reef mesopredatory fish - Alastair R. Harborne; David P. Kochan; Melanie M. Esch; Robert Y. Fidler; Matthew D. Mitchell; Drew W. Butkowski; Manuel González‐Rivero (Journal of Fish Biology, 2022)
The habitat preferences of many reef fishes are well established, but the use of space within these habitats by non‐site‐attached species is poorly studied. The authors examined the space use of a functionally important mesopredator, graysby ( Cephalopholis cruentata ), on six patch reefs in the Florida Keys. A 1 m 2 ‐scale grid was constructed on each reef and 16 individual C. cruentata were tracked diurnally in situ to identify space use. At the patch reef scale, larger C. cruentata were more active and had larger observed home ranges, although home ranges were also affected by fish density and the abundances of prey and predators. The total time in each 1 m 2 grid cell was regressed against a range of fine‐scale biotic variables, including multiple variables derived from structure‐from‐motion three‐dimensional digital reconstructions of each reef. Nonetheless, time in grid cells (preferred microhabitats) was only significantly positively correlated with the height of carbonate structures, likely because the cavities they enclose are particularly suitable for predator avoidance, resting and ambushing prey. The ongoing flattening of reefs in the region caused by negative carbonate budgets is thus likely to have significant effects on the abundance and space use of C. cruentata . In addition to examining spatial patterns, we analysed C. cruentata waiting times in each grid cell before moving. These times were best approximated by a truncated power‐law (heavy‐tailed) distribution, indicating a “bursty” pattern of relatively long periods of inactivity interspersed with multiple periods of activity. Such a pattern has previously been identified in a range of temperate ambush predators, and the authors extend this move‐wait behaviour, which may optimize foraging success, to a reef fish for the first time. Understanding how C. cruentata uses space and time is critical to fully identify their functional role and better predict the implications of fishing and loss of reef structure.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Summer Oxygen Dynamics on a Southern Arabian Gulf Coral Reef - Alain de Verneil; John A. Burt; Matthew Mitchell; Francesco Paparella (Frontiers in Marine Science, 2021)
During the summer the Arabian Gulf is the world's warmest sea, also characterized by hypersalinity and extreme annual temperature fluctuations (12–35 o C), making it marginal for coral growth. Yet extensive reefs occur in all eight nations bordering the Gulf. Here we present data demonstrating recurrent summer hypoxia events [oxygen concentration (O 2 ) <2 mg l −1 ] at a reef in the southern Gulf. Currently these episodes are short enough (median 3 h, max 10 h) to preclude mass mortality. Will this always be the case? Predicting future Gulf hypoxia risk for coral reef ecosystems requires diagnosing the underlying causes driving the timing and magnitude of O 2 swings. To this end, we compare our data with the output of a simple coupled 1-D water column/biogeochemical model of the reef environment. This allows us to give quantitative estimates of the O 2 fluxes produced by photosynthesis both in the water column and within the coral framework, by respiration processes in the benthos, and from the atmosphere. We demonstrate the role of turbulent mixing, and in particular of tides, in shaping the temporal variability of the amplitude of the diel O 2 cycle. We find that, in spite of significant turbulent mixing, which maintains the temperature vertically well-mixed, the biological O 2 production and consumption is dominant over the atmospheric O 2 flux, and is sufficient to generate vertical differences of 1 to 5 mg l −1 between the bottom and 1.5 m above it. While estimating future trends of hypoxia frequency will require further study, the present findings single out the relevant physical and biological processes (and their interplay) which deserve further scrutiny. The Gulf today experiences temperatures expected to occur across much of the tropics by the end of the century, and the observation of recurrent hypoxia events in the Gulf suggests that similar hypoxic phenomena may represent an important, but to date underappreciated, threat to the future of global coral reefs.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

Correction to: Drying microclimates threaten persistence of natural and translocated populations of threatened frogs - Emily P. Hoffmann; Kim Williams; Matthew R. Hipsey; Nicola J. Mitchell (Biodiversity and Conservation, 2021)

Drying microclimates threaten persistence of natural and translocated populations of threatened frogs - Emily P. Hoffmann; Kim Williams; Matthew R. Hipsey; Nicola J. Mitchell (Biodiversity and Conservation, 2021)
Defining species habitat requirements is essential for effective conservation management through revealing agents of population decline and identifying critical habitat for conservation actions, such as translocations. Here we studied the habitat-associations of two threatened terrestrial-breeding frog species from southwestern Australia, Geocrinia alba and Geocrinia vitellina , to investigate if fine-scale habitat variables explain why populations occur in discrete patches, why G. alba is declining, and why translocation attempts have had mixed outcomes. We compared habitat variables at sites where the species are present, to variables at immediately adjacent sites where frogs are absent, and at sites where G. alba is locally extinct. Dry season soil moisture was the most important predictor of frog abundance for both species, and explained why G. alba had become extinct from some areas. Sites where G. alba were present were also positively associated with moss cover, and negatively with bare ground and soil conductivity. Modelling frog abundance based exclusively on dry season soil moisture predicted recent translocation successes with high accuracy. Hence, considering dry season soil moisture when selecting future translocation sites should increase the probability of population establishment. We propose that a regional drying trend is the most likely cause for G. alba declines and that both species are at risk of further habitat and range contraction due to further projected regional declines in rainfall and groundwater levels. More broadly, our study highlights that conservation areas in drying climates may not provide adequate protection and may require interventions to preserve critical habitat.

In Vivo Differentiation of Stem Cell-derived Human Pancreatic Progenitors to Treat Type 1 Diabetes - Mitchell H. Maloy; Matthew A. Ferrer; Natesh Parashurama (Stem Cell Reviews and Reports, 2020)

Evaluating a Rapid Field Assessment System for Anticoagulant Rodenticide Exposure of Raptors - Ariana J. Dickson; James R. Belthoff; Kristen A. Mitchell; Brian W. Smith; Zachary P. Wallace; Matthew J. Stuber; Michael J. Lockhart; Barnett A. Rattner; Todd E. Katzner (Archives of Environmental Contamination and Toxicology, 2020)

Ecometrics and the paleoecological implications of Pleistocene faunas from the western coastal plains of the Cape Floristic Region, South Africa - J. Tyler Faith; David R. Braun; Benjamin Davies; Larisa R. G. DeSantis; Matthew J. Douglass; Irene Esteban; Vincent Hare; Naomi E. Levin; Julie Luyt; Robyn Pickering; Mitchell J. Power; Judith Sealy; et al. (Journal of Quaternary Science, 2020)
The Pleistocene ungulate communities from the western coastal plains of South Africa's Cape Floristic Region (CFR) are diverse and dominated by grazers, in contrast to the region's Holocene and historical faunas, which are relatively species‐poor and dominated by small‐bodied browsers and mixed feeders. An expansion of grassy habitats is clearly implied by the Pleistocene faunas, but the presence of ruminant grazers that cannot survive the summer dry season typical of the region today suggests other important paleoecological changes. Here we use dental ecometrics to explore the paleoecological implications of the region's Pleistocene faunas. We show that the dental traits (hypsodonty and occlusal topography) of the ungulates that occurred historically in the CFR track annual and summer aridity, and we use these relationships to reconstruct past aridity. Our results indicate that the Pleistocene faunas signal paleoenvironments that were on average less arid than today, including during the summer, consistent with other lines of evidence that suggest a higher water table and expansion of well‐watered habitats. Greater water availability can be explained by lower temperature and reduced evapotranspiration during cooler phases of the Pleistocene, probably coupled with enhanced groundwater recharge due to increased winter precipitation.

Two-Photon Polymerisation 3D Printing of Microneedle Array Templates with Versatile Designs: Application in the Development of Polymeric Drug Delivery Systems - Ana Sara Cordeiro; Ismaiel A. Tekko; Mohamed H. Jomaa; Lalitkumar Vora; Emma McAlister; Fabiana Volpe-Zanutto; Matthew Nethery; Paul T. Baine; Neil Mitchell; David W. McNeill; Ryan F. Donnelly (Pharmaceutical Research, 2020)
Purpose To apply a simple and flexible manufacturing technique, two-photon polymerisation (2PP), to the fabrication of microneedle (MN) array templates with high precision and low cost in a short time. Methods Seven different MN array templates were produced by 2PP 3D printing, varying needle height (900–1300 μm), shape (conical, pyramidal, cross-shaped and with pedestal), base width (300–500 μm) and interspacing (100–500 μm). Silicone MN array moulds were fabricated from these templates and used to produce dissolving and hydrogel-forming MN arrays. These polymeric MN arrays were evaluated for their insertion in skin models and their ability to deliver model drugs (cabotegravir sodium and ibuprofen sodium) to viable layers of the skin (ex vivo and in vitro) for subsequent controlled release and/or absorption. Results The various templates obtained with 2PP 3D printing allowed the reproducible fabrication of multiple MN array moulds. The polymeric MN arrays produced were efficiently inserted into two different skin models, with sharp conical and pyramidal needles showing the highest insertion depth values (64–90% of needle height). These results correlated generally with ex vivo and in vitro drug delivery results, where the same designs showed higher drug delivery rates after 24 h of application. Conclusion This work highlights the benefits of using 2PP 3D printing to prototype variable MN array designs in a simple and reproducible manner, for their application in drug delivery.

Non-consumptive effects in fish predator–prey interactions on coral reefs - Matthew D. Mitchell; Alastair R. Harborne (Coral Reefs, 2020)

Dietary Ecology of the Nigeria–Cameroon Chimpanzee (Pan troglodytes ellioti) - Ekwoge E. Abwe; Bethan J. Morgan; Roger Doudja; Fabrice Kentatchime; Flaubert Mba; Alvine Dadjo; Dana M. Venditti; Matthew W. Mitchell; Bernard Fosso; Albert Mounga; Roger C. Fotso; Mary Katherine Gonder (International Journal of Primatology, 2020)

Rosette core fungal resistance in Arabidopsis thaliana - Yanwan Dai; Huw A. Ogilvie; Yuan Liu; Michael Huang; Lye Meng Markillie; Hugh D. Mitchell; Eli J. Borrego; Michael V. Kolomiets; Matthew J. Gaffrey; Galya Orr; E. Wassim Chehab; Wan-Ting Mao; et al. (Planta, 2019)

Assessing ecosystem service trade-offs and synergies: The need for a more mechanistic approach - Marie C. Dade; Matthew G.E. Mitchell; Clive A. McAlpine; Jonathan R. Rhodes (Ambio, 2019)

The Effects of Selenomethionine on the Escape Behaviours of Fathead Minnows - Philip J. Anderson; Matthew D. Mitchell; Katherine J. Fedoroff; Douglas P. Chivers; Maud C. O. Ferrari (Archives of Environmental Contamination and Toxicology, 2019)

Male-Driven Differences in Chimpanzee (Pan troglodytes) Population Genetic Structure Across Three Habitats in Cameroon and Nigeria - Matthew W. Mitchell; Sabrina Locatelli; Ekwoge E. Abwe; Lora Ghobrial; Mary Katherine Gonder (International Journal of Primatology, 2018)

Computational Model for Hyperfibrinolytic Onset of Acute Traumatic Coagulopathy - Tie Bo Wu; Sheng Wu; Matthew Buoni; Thomas Orfeo; Kathleen Brummel-Ziedins; Mitchell Cohen; Linda Petzold (Annals of Biomedical Engineering, 2018)

The putative leucine sensor Sestrin2 is hyperphosphorylated by acute resistance exercise but not protein ingestion in human skeletal muscle - Nina Zeng; Randall F. D’Souza; Brie Sorrenson; Troy L. Merry; Matthew P. G. Barnett; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2018)

A pharmacokinetic model for amiodarone in infants developed from an opportunistic sampling trial and published literature data - Samantha H. Dallefeld; Andrew M. Atz; Ram Yogev; Janice E. Sullivan; Amira Al-Uzri; Susan R. Mendley; Matthew Laughon; Christoph P. Hornik; Chiara Melloni; Barrie Harper; Andrew Lewandowski; Jeff Mitchell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Spatiotemporal Models of an Estuarine Fish Species to Identify Patterns and Factors Impacting Their Distribution and Abundance - Leo Polansky; Ken B. Newman; Matthew L. Nobriga; Lara Mitchell (Estuaries and Coasts, 2018)

The Scale-Dependent Role of Biological Traits in Landscape Ecology: A Review - Andrés Felipe Suárez-Castro; Jeremy S. Simmonds; Matthew G. E. Mitchell; Martine Maron; Jonathan R. Rhodes (Current Landscape Ecology Reports, 2018)

Confirmation of a unique and genetically diverse ‘heritage’ strain of brook trout (Salvelinus fontinalis) in a remote Adirondack watershed - Spencer A. Bruce; Matthew P. Hare; Matthew W. Mitchell; Jeremy J. Wright (Conservation Genetics, 2018)

Erratum to: Structural characterization of an all-aminosugar-containing capsular polysaccharide from Colwellia psychrerythraea 34H - Angela Casillo; Jonas Ståhle; Ermenegilda Parrilli; Filomena Sannino; Daniel E. Mitchell; Giuseppina Pieretti; Matthew I. Gibson; Gennaro Marino; Rosa Lanzetta; Michelangelo Parrilli; Göran Widmalm; Maria L. Tutino; et al. (Antonie van Leeuwenhoek, 2017)

Structural characterization of an all-aminosugar-containing capsular polysaccharide from Colwellia psychrerythraea 34H - Angela Casillo; Jonas Ståhle; Ermenegilda Parrilli; Filomena Sannino; Daniel E. Mitchell; Giuseppina Pieretti; Matthew I. Gibson; Gennaro Marino; Rosa Lanzetta; Michelangelo Parrilli; Göran Widmalm; Maria L. Tutino; et al. (Antonie van Leeuwenhoek, 2017)

Using high-resolution LiDAR data to quantify the three-dimensional structure of vegetation in urban green space - Rhiannon J. C. Caynes; Matthew G. E. Mitchell; Dan Sabrina Wu; Kasper Johansen; Jonathan R. Rhodes (Urban Ecosystems, 2016)

Diet cues alter the development of predator recognition templates in tadpoles - Matthew D. Mitchell; Maud C. O. Ferrari; Tyrone Lucon-Xiccato; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2016)

A major QTL corresponding to the Rk locus for resistance to root-knot nematodes in cowpea (Vigna unguiculata L. Walp.) - Bao-Lam Huynh; William C. Matthews; Jeffrey D. Ehlers; Mitchell R. Lucas; Jansen R. P. Santos; Arsenio Ndeve; Timothy J. Close; Philip A. Roberts (Theoretical and Applied Genetics, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Whole-exome sequencing identifies novel ECHS1 mutations in Leigh syndrome - Martine Tetreault; Somayyeh Fahiminiya; Hana Antonicka; Grant A. Mitchell; Michael T. Geraghty; Matthew Lines; Kym M. Boycott; Eric A. Shoubridge; John J. Mitchell; Jacques L. Michaud; Jacek Majewski (Human Genetics, 2015)

Circulating acylcarnitines as biomarkers of mitochondrial dysfunction after acetaminophen overdose in mice and humans - Mitchell R. McGill; Feng Li; Matthew R. Sharpe; C. David Williams; Steven C. Curry; Xiaochao Ma; Hartmut Jaeschke (Archives of Toxicology, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

Climate change mitigation policy paradigms—national objectives and alignments - Kirsten Halsnæs; Amit Garg; John Christensen; Helene Ystanes Føyn; Maryna Karavai; Emilio La Rovere; Matthew Bramley; Xianli Zhu; Catherine Mitchell; Joyashree Roy; Kanako Tanaka; Hidefumi Katayama; et al. (Mitigation and Adaptation Strategies for Global Change, 2014)

TESS Ad-Mixer: A novel program for visualizing TESS Q matrices - Matthew W. Mitchell; Brian Rowe; Paul R. Sesink Clee; Mary Katherine Gonder (Conservation Genetics Resources, 2013)

Disturbance and the role of refuges in mediterranean climate streams - Belinda J. Robson; Edwin T. Chester; Bradley D. Mitchell; Ty G. Matthews (Hydrobiologia, 2013)

Light and nutrient control of photosynthesis in natural phytoplankton populations from the Chukchi and Beaufort seas, Arctic Ocean - Molly A. Palmer; Gert L. van Dijken; B. Greg Mitchell; Brian J. Seegers; Kate E. Lowry; Matthew M. Mills; Kevin R. Arrigo (Limnology and Oceanography, 2013)
During the 2010–2011 ‘Impacts of Climate Change on the EcoSystems and Chemistry of the Arctic Pacific Environment’ project, we measured photosynthetic parameters in natural Arctic phytoplankton assemblages from the Chukchi and Beaufort seas. Water‐column samples were taken from the near surface (3.1 ± 0.9 m) and subsurface (28 ± 10.3 m) at ∼ 85 stations each year representing a wide range of ecological conditions, including under sea ice (UI) and in open water (OW). The physiological response of phytoplankton to light was used to assess photo‐acclimation, photosynthetic efficiency, and maximum chlorophyll a (Chl a ) normalized rates of carbon fixation. Phytoplankton from the subsurface were acclimated to lower irradiance, as evidenced by higher photosynthetic efficiencies ( α * ), reduced mean absorption spectra ( ā * ) associated with heavy pigment packaging, higher maximum quantum yields of photosynthesis (Φ m ), increased Chl a content (Chl a : POC), and higher potential growth rates ( μ m ) than surface samples. In addition, phytoplankton growing in the UI subsurface had higher μ m , increased Φ m , and higher Chl a content, as well as reduced ā * compared with those found in OW. P * m did not vary between habitats despite vastly different nutrient and light conditions (averaging ∼ 1 mg C mg −1 Chl a h −1 ), except where nitrate exceeded > 10 mg m −3 , in which case P * m averaged 5–6 mg C mg −1 Chl a h −1 . Results from a stepwise regression analysis of photosynthetic parameters vs. environmental factors indicate that the concentration of inorganic nitrogen (significant relationships with P * m , α * , Φ m , μ m , and Chl a : POC) and temperature at sample depth (a strong indicator of habitat type; significant relationship with β * , ā * , Φ m , μ m , and Chl a : POC) are the best predictors of photosynthetic variables. In addition, the amount of light available at sample depth significantly predicted both E k and Chl a : POC. Our results suggest that it is the balance between light and nutrient availability in the various environments encountered in the seasonal sea ice zone that result in the pattern of photo‐physiological data presented here. A significant proportion of primary production has now been observed to occur under the sea ice; therefore, our results may be a change from prior conditions in the region.

Linking Landscape Connectivity and Ecosystem Service Provision: Current Knowledge and Research Gaps - Matthew G. E. Mitchell; Elena M. Bennett; Andrew Gonzalez (Ecosystems, 2013)

Ontogenetic differences in chemical alarm cue production determine antipredator responses and learned predator recognition - Matthew D. Mitchell; Mark I. McCormick (Behavioral Ecology and Sociobiology, 2013)

Remucal et al. Respond: - Jonathan M. Remucal; Jason D. McGee; Matthew M. Fehrenbacher; Constance Best; Robert J. Mitchell (Journal of Forestry, 2013)

Multiple environmental stressors elicit complex interactive effects in the western fence lizard (Sceloporus occidentalis) - Craig A. McFarland; Larry G. Talent; Michael J. Quinn; Matthew A. Bazar; Mitchell S. Wilbanks; Mandana Nisanian; Robert M. Gogal; Mark S. Johnson; Edward J. Perkins; Kurt A. Gust (Ecotoxicology, 2012)

The influence of socioeconomic, environmental, and demographic factors on municipality-scale land-cover change in Mexico - Martha Bonilla-Moheno; T. Mitchell Aide; Matthew L. Clark (Regional Environmental Change, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Effects of chronic and intermittent cocaine treatment on dominance, aggression, and oxytocin levels in post-lactational rats - Josephine M. Johns; Matthew S. McMurray; Paul W. Joyner; Thomas M. Jarrett; Sarah K. Williams; Elizabeth T. Cox; Mitchell A. Black; Christopher L. Middleton; Cheryl H. Walker (Psychopharmacology, 2010)

Barcoding bushmeat: molecular identification of Central African and South American harvested vertebrates - Mitchell J. Eaton; Greta L. Meyers; Sergios-Orestis Kolokotronis; Matthew S. Leslie; Andrew P. Martin; George Amato (Conservation Genetics, 2010)

Efficacy of exclusion fencing to protect ephemeral floodplain lagoon habitats from feral pigs (Sus scrofa) - Robert G. Doupé; Jim Mitchell; Matthew J. Knott; Aaron M. Davis; Alan J. Lymbery (Wetlands Ecology and Management, 2010)

Plant interactions are unimportant in a subarctic–alpine plant community - Matthew G. E. Mitchell; James F. Cahill; David S. Hik (Ecology, 2009)
We investigated whether plant interaction intensity in a subarctic–alpine meadow is important for determining community structure and species abundance. Using two common species as phytometers, we measured interaction intensity using a neighbor removal approach. Eight biotic and abiotic variables known to influence species abundance and community structure were measured, with regression trees used to examine how plant interactions and the biotic and abiotic variables were related to species evenness, richness, and phytometer spatial cover. A range of interactions was present, with both strong competition and facilitation present over small‐scale abiotic and biotic gradients. Despite the variation in interaction intensity, it was generally unrelated to either community structure or phytometer cover. In other words, plant interactions were intense in many cases but were not important to community structure. This may be due to the prevalence of clonal species in this system and the influence of previous year's interactions on plant survival and patterns of community structure. These results also suggest how conflicting theories of the role of competition in unproductive environments may be resolved. Our findings suggest that plant interactions may be intense in reducing individual growth, while simultaneously not important in the context of community structure. Plant interactions need to be viewed and tested relative to other factors and stresses to accurately evaluate their importance in plant communities, with continued differentiation between the intensity of plant interactions and their relative importance in communities.

Risk Management in the Pharmaceutical Product Development Process - Matthew H. Hulbert; Liam C. Feely; Eugene L. Inman; Alton D. Johnson; Albert S. Kearney; James Michaels; Michael Mitchell; Elena Zour (Journal of Pharmaceutical Innovation, 2008)

Minimizing Variability of Cascade Impaction Measurements in Inhalers and Nebulizers - Matthew Bonam; David Christopher; David Cipolla; Brent Donovan; David Goodwin; Susan Holmes; Svetlana Lyapustina; Jolyon Mitchell; Steve Nichols; Gunilla Pettersson; Chris Quale; Nagaraja Rao; et al. (AAPS PharmSciTech, 2008)

Purification and characterization of rhodobactin: a mixed ligand siderophore from Rhodococcus rhodochrous strain OFS - Suraj Dhungana; Ryszard Michalczyk; Hakim Boukhalfa; Joseph G. Lack; Andrew T. Koppisch; Jason M. Fairlee; Mitchell T. Johnson; Christy E. Ruggiero; Seth G. John; Matthew M. Cox; Cindy C. Browder; Jennifer H. Forsythe; et al. (BioMetals, 2007)

Nocturnal foraging by great skuas Stercorarius skua: implications for conservation of storm-petrel populations - Stephen C. Votier; Jonathan E. Crane; Stuart Bearhop; Ana de León; Claire A. McSorley; Eduardo Mínguez; Ian P. Mitchell; Matthew Parsons; Richard A. Phillips; Robert W. Furness (Journal of Ornithology, 2006)

Axial mixing in rotating drums using magnetic resonance imaging using bran as a model for solid state fermentations - Matthew T. Hardin; Tony Howes; David A. Mitchell; Andrew K. Whittaker (Biotechnology Letters, 2002)

Extending the Boundaries of Life‐Cycle Assessment through Environmental Economic Input‐Output Models - H. Scott Matthews; Mitchell J. Small (Journal of Industrial Ecology, 2000)